(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The topic of the article are vehicle restraint systems. Specifically, the paper focuses on the safety analysis of the way of implementation of crash cushions. Within the safety analysis carried out on the territory of the Ústí Region of the Czech Republic, the most frequently occurring deficiencies in crash cushions and their possible impacts on road safety were identified. The output is the creation of catalogue sheets of crash cushions, which contain the most frequently installed crash cushions on the road network and a summary of methodological requirements for their adequate implementation. The work is intended to serve as an effective tool and a quality source of information for road managers and road safety auditors during their subsequent inspection.